Strategic applications of methylene thioacetal bonds as disulfide surrogates in peptide drug discovery - Zhou, Yaqi; Wang, Dongyuan; Xu, Jiean; Zheng, Nan (Frontiers in Chemistry, 2025)
Disulfide bonds are indispensable structural motifs in bioactive peptides, stabilizing conformations which are critical for molecular recognition and biological activity. However, their intrinsic chemical lability under physiological and manufacturing conditions has long presented challenges in peptide drug development. Efforts to address these limitations have yielded a diverse array of disulfide bond surrogates, each with distinct advantages and constraints. Among these, methylene thioacetal linkages have recently emerged as a particularly promising method offering a favorable balance of structural fidelity, synthetic accessibility, and chemical stability. This review summarizes the biological importance and limitations of native disulfide bonds, surveys established strategies for disulfide bond mimicry, and provide a comprehensive summary of research leveraging methylene thioacetal chemistry as an emerging tool in the design of next-generation peptide therapeutics.